The Influence of Religiosity and Report Transparency on ASN Motivation in Paying Professional Zakat at the Regional Secretariat of East Lombok Regency - Mulyadi Mulyadi; Musawar Musawar; Muh. Azkar (STKIP Taman Siswa Bima, 2025)
Religiosity is a factor in the individual and everyone has a different understanding in carrying out and implementing religious teachings. Transparency aims to provide information to the public that the public has the right to know financial information which is proven honestly and openly.Someone who issued his zakat meant that he has cleaned himself, his soul and his property. So it can be concluded that religiosity and transparency are important factors in determining awareness of muzakki on the motivation to pay zakat at zakat management institutions. The objective of this research was to determine the influence of religiosity and transparency on the motivation of the State Civil Apparatur in paying professional zakat at the Regional Secretariat of East Lombok Regency. The method used in this research was descriptive quantitative. Hypothesis testing used multiple linier regression analysis method and classical assumption testing on 50 respondents. The sampling technique used was nonprobability sampling with the type of purposive sampling, namely a sampling technique with the consideration that the respondents were persons who were predicted to be obliged to pay zakat. The results of this research showed that te religiosity and transparency had significant and positive influences on the motivation of the State Civil Apparatur in paying professional zakat. This was evidenced by the significant score obtained which was smaller than 0,05 fron each variable.